RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND JOB SATISFACTION OF NURSES AT MUHAMMADIYAH BABAT LAMONGAN HOSPITAL - Alifia Meliana Ramadhani; Suratmi Suratmi; Nurul Hikmatul Qowi (Universitas Airlangga, 2023)
Introduction: One of the problems that is prone to occur among nurses is job satisfaction. Good job satisfaction includes good relationships with fellow colleagues and the surrounding environment will create a friendly and good atmosphere so that a person feels comfortable and becomes attached to his work. The purpose of this research is to determine the relationship between employe engagement with the job satisfaction of nurses at the Muhammadiyah Babat General Hospital. Methods:The research used in this study was analytic correlation with a cross sectional approach using cluster sampling technique to get 48 respondents. This research used a closed questionnaire and analyzed using the Spearman test. Results: This study found that the results of employe engagement or employee engagement with nurses at Babat Lamongan General Hospital were mostly high, with 25 nurses (52.1%) and most of them had moderate job satisfaction with as many as 28 nurses (58.3). Conclusions:Based on the results of the analysis using the Spearman Rho test, it was found that the value of p = 0.000 (p <0.05) and the value of ð”‘Ÿ = 0.557, then H1 is accepted. This means that there is a relationship between Employe Engagement and Job Satisfaction of nurses at Muhammadiyah Babat General Hospital. Based on this research it is expected that nurses can increase their work productivity, as well as support each other and love their work more.